VLX1570 induces apoptosis through the generation of ROS and induction of ER stress on leukemia cell lines. Issue 8 (13th June 2021) - Kurozumi, Nami; Tsujioka, Takayuki; Ouchida, Mamoru; Sakakibara, Kanae; Nakahara, Takako; Suemori, Shin‐ichiro; Takeuchi, Masaki; Kitanaka, Akira; Shibakura, Misako; Tohyama, Kaoru
Abstract: A novel proteasome deubiquitinase inhibitor, VLX1570, has been highlighted as a promising therapeutic agent mainly for lymphoid neoplasms and solid tumors. We examined in vitro effects of VLX1570 on eight myeloid and three lymphoid leukemia cell lines. From cell culture studies, 10 out of 11 cell lines except K562 were found to be susceptible to VLX1570 treatment and it inhibited cell growth mainly by apoptosis. Next, to identify the signaling pathways associated with apoptosis, we performed gene expression profiling using HL‐60 with or without 50 nmol/L of VLX1570 for 3 hours and demonstrated that VLX1570 induced the genetic pathway involved in "heat shock transcription factor 1 (HSF1) activation", "HSF1 dependent transactivation", and "Regulation of HSF1 mediated heat shock response". VLX1570 increased the amount of high molecular weight polyubiquitinated proteins and the expression of HSP70 as the result of the suppression of ubiquitin proteasome system, the expression of heme oxygenase‐1, and the amount of phosphorylation in JNK and p38 associated with the generation of reactive oxygen species (ROS) induced apoptosis and the amount of phosphorylation in eIF2α, inducing the expression of ATF4 and endoplasmic reticulum (ER) stress dependent apoptosis protein, CHOP, and the amount of phosphorylation slightly in IRE1α, leading to increased expression of XBP‐1s in leukemia cell lines. In the present study, we demonstrate that VLX1570 induces apoptosis and exerts a potential anti‐leukemic effect through the generation of ROS and induction of ER stress in leukemia cell lines. Abstract : VLX1570 induces apoptosis mainly through reactive oxygen (ROS) stress signaling and unfolded protein response pathway under endoplasmic reticulum (ER) stress. Regarding ER stress, VLX1570 activated the protein kinase RNA‐like endoplasmic reticulum kinase signaling pathway, leading to ER stress‐dependent apoptosis. As another pathway, excess accumulation of polyubiquitinated proteins on the mitochondria induces ROS generation, followed by phosphorylation of JNK and p38, leading to caspases‐dependent apoptosis.